2017
DOI: 10.1155/2017/2304218
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms inToll-Like Receptors 4and9with Autoimmune Thyroid Disease in Korean Pediatric Patients

Abstract: Background Toll-like receptors (TLRs) have been suggested to be associated with the development of AITD. Methods Fifteen single-nucleotide polymorphisms in 7 TLR genes were analyzed in 104 Korean children (girls = 86, boys = 18) with AITD (Hashimoto disease (HD) = 44, Graves' disease (GD) = 60, thyroid-associated ophthalmopathy (TAO) = 29, and non-TAO = 31) with 183 controls. Results GD showed higher frequencies of the TLR4 rs1927911 C allele than control. TAO showed a lower frequency of the TLR4 rs1927911 CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…Associated with psoriatic arthritis risk 69 , hip and knee osteoarthritis 70,71 , SLE 72 and IBD 73 ; associated with the risk of autoimmune thyroid disease 74 ; response to anti-TNF therapy in patients with RA 64 34 and DNA samples were obtained from peripheral blood collected at the Statens Serum Institut (Copenhagen, Denmark), which routinely perform screening for tuberculosis before treatment with biological treatments. Healthy blood donors were recruited in Viborg and Sønderborg (Denmark).…”
Section: Ra Patient Populationsmentioning
confidence: 99%
“…Associated with psoriatic arthritis risk 69 , hip and knee osteoarthritis 70,71 , SLE 72 and IBD 73 ; associated with the risk of autoimmune thyroid disease 74 ; response to anti-TNF therapy in patients with RA 64 34 and DNA samples were obtained from peripheral blood collected at the Statens Serum Institut (Copenhagen, Denmark), which routinely perform screening for tuberculosis before treatment with biological treatments. Healthy blood donors were recruited in Viborg and Sønderborg (Denmark).…”
Section: Ra Patient Populationsmentioning
confidence: 99%
“…Most recently, based on the results of an analysis performed in a large cohort of GD patients, Yuan et al reported significant genetic heterogeneity between subjects with age of GD onset ≤20 and >20 years, suggesting it is reasonable to reduce the cut‐off value for the definition of early‐onset GD. However, data on the genetic risk factors in POGD are limited . In our multicentre study, we collected a large group of POGD patients and investigated similarities and differences in the genetic background between POGD and AOGD for the established and suggested GD/AITD risk loci .…”
Section: Introductionmentioning
confidence: 99%
“…However, data on the genetic risk factors in POGD are limited. [18][19][20][21][22][23][24][25][26][27] In our multicentre study, we collected a large group of POGD patients and investigated similarities and differences in the genetic background between POGD and AOGD for the established and suggested GD/ AITD risk loci. Subsequently, we looked for genetic variants associated with age of GD onset in the entire cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 encodes toll like receptor 4, plays a role in stimulating immune reactions. Furthermore, TLR-9 rather than TLR-4 gene polymorphisms are related to increased susceptibility of TED (44), and may contribute to the pathogenesis of TED in children (45). The results of our study indicated that TLR4, a hub gene, is down-regulated in TED orbital adipose tissues.…”
Section: Discussionmentioning
confidence: 59%